2017
DOI: 10.1007/s10620-017-4707-7
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel IBS Patients Have Higher Incidence of Gastrointestinal Symptoms Influenced by Age and Gender

Abstract: Background Clopidogrel is an irreversible antagonist of P2Y12 receptors (P2Y12Rs) used as an antiplatelet drug to reduce risk of thrombosis. P2Y12Rs are expressed in gastrointestinal (GI) tract where they might regulate GI function. Aim To evaluate if blockade of P2Y12Rs by clopidogrel is associated with higher incidence of GI symptoms in patients with irritable bowel syndrome (IBS). Methods A retrospective analysis of our institutional database was conducted for a 13-year period. IBS patients were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Both drugs are irreversibly bound to P2Y12 receptors to produce an antiplatelet effect, whereas ticagrelor, a reversible inhibitor, does not require bioactivation 17 . In a previous study, irreversible inhibition of P2Y12 receptors was hypothesized to be responsible for the overstimulation of gut reflexes 18 . These pharmacokinetic differences combined with angiogenic factors inhibition 9,10 may produce a distinct GI bleeding risk based on the P2Y12 inhibitor used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both drugs are irreversibly bound to P2Y12 receptors to produce an antiplatelet effect, whereas ticagrelor, a reversible inhibitor, does not require bioactivation 17 . In a previous study, irreversible inhibition of P2Y12 receptors was hypothesized to be responsible for the overstimulation of gut reflexes 18 . These pharmacokinetic differences combined with angiogenic factors inhibition 9,10 may produce a distinct GI bleeding risk based on the P2Y12 inhibitor used.…”
Section: Methodsmentioning
confidence: 99%
“… 17 In a previous study, irreversible inhibition of P2Y12 receptors was hypothesized to be responsible for the overstimulation of gut reflexes. 18 These pharmacokinetic differences combined with angiogenic factors inhibition 9 , 10 may produce a distinct GI bleeding risk based on the P2Y12 inhibitor used.…”
Section: Methodsmentioning
confidence: 99%
“…Clopidogrel can be used alone by patients who require secondary stroke prevention or have and intolerance of aspirin and by children. 5,14,15 It mainly works by blocking the platelet P2Y12 receptor to exert antiplatelet effects. Anderson et al found that the antiplatelet effect of clopidogrel activated before standard accepted biotransformation pathways.…”
Section: Discussionmentioning
confidence: 99%